Utilization of Digital Marketing for MSMEs in the Production of Knitted Bags in Lembang, West Bandung Regency - Saepulloh, Yusep; Alijoyo, Franciskus Antonius (Yayasan Azka Hafidz Maulana, 2024)
The change in marketing system from traditional to digital marketing to face the 5.0 era forces MSMEs to make changes to their product marketing system through social media. Based on this, there are still many MSME players who do not understand digital marketing. For this reason, the aim of this research is to examine the use of digital marketing in accelerating the growth of Micro, Small and Medium Enterprises (MSMEs) in Lembang District, West Bandung. The focus of this study lies in how digital marketing strategies can be integrated into MSME business processes to increase visibility, market access, and ultimately, business performance. Using a mixed methodology approach, this research collects and analyzes data, in-depth interviews, and case studies of several MSMEs in the area. The research results show that the adoption of digital marketing, including the use of social media, search engine optimization (SEO), and content marketing, significantly contributes to increasing sales and brand building for MSMEs. Furthermore, this research identifies the challenges and opportunities faced by MSMEs in implementing digital marketing strategies, including limited resources, the need to increase digital competence, and digital market potential that has not been fully exploited. The conclusions of this study offer strategic insights for MSME owners, digital marketing practitioners, and policy makers to design and implement more effective digital marketing initiatives, thereby encouraging local economic growth and increasing the competitiveness of MSMEs in the global market